Incorporare l’attività sportiva: il caso dell’athleisure tra immagine di sé e neoliberismo - Cereda, Ambrogia (Eracle. Journal of Sport and Social Sciences, 2023)
Mainly referred to the combinations of sportswear in daily life, athleisure (a crasis of the terms athletic and leisure) has enormously spread in Western society during the recent years of the pandemics and it has become a growing economic sector, which has been studied from a prominently marketing perspective. The article will provide a more accurate and complex insight of the phenomenon from a cultural perspective, focusing on the ways in which the cultural representation of the active athletic body is materialized via athleisure, intertwined with gender identity, and embodied in everyday practice.